Pengujian Gasifikasi Updraft Untuk Tongkol Jagung dan Cangkang Mete Sebagai Sumber Energi Alternatif - Taufik, Muhamad Rian; Mangalla, Lukas Kano; Barata, La Ode Ahmad (Teknik Mesin Universitas Halu Oleo, 2021)
Gasification is the process of converting energy from fuel containing carbon (solid or liquid) into a gas called syngas (synthesis gas). The purpose of this study was to determine the characteristics of syngas resulting from the gasification of a mixture of corn cobs and cashew shells and to determine the ideal composition of a mixture of corn cobs and cashew shells that produces optimal gas ingredients. The method used in this study is an experimental method by making a gasification tool and taking data directly with several variations of composition. The results showed that thecharacteristics syngas at the composition of 100% corn cobs could not produce flames, the mixture composition of 75% corn cobs and 25% cashew shells could not produce flames, at the composition of a mixture of 50% corn cobs and 50% cashew shells it was able to produce flames. flame, the composition of a mixture of 25% corn cobs and 75% cashew shells can already produce a flame and a composition of 100% cashew shells can also produce a gasification flame. Virtually the resulting flame is thought to be due to the presence of more hydrogen (gas) than carbon (smoke from combustion). The best composition in updraft gasification testing for corn cobs and cashew shells was obtained in a composition with a mixture of 25% corn cobs and 75% cashew shells, the resulting flame was obtained at 32.5 minutes to 50 minutes. Key words: Updraft gasification, composition , corn cobs, cashew shells, flame